Solution:
A function with an input of 1 has an output of 3.
This means that
![when\text{ }x=1,y=3](https://img.qammunity.org/2023/formulas/mathematics/college/fzlg55q7wydawx40gue1weye63ah5qfhdd.png)
Step 1:
We will try the first option
![\begin{gathered} y=3x \\ y=3(1) \\ y=3 \\ (1,3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qf8omxii9lum15pmsxopvv87ao847slbst.png)
Step 2:
We will try the second option
![\begin{gathered} y=-x+4 \\ y=-1+4 \\ y=3 \\ (1,3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bxp1uvk0zzpob43e6pcq6ljeaw6k36hxty.png)
Step 3:
We will try the third option
![\begin{gathered} y=x-2 \\ y=1-2 \\ y=-1 \\ (1,-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8yg25jam1snmdhfeb5o3wfwis56yu258b4.png)
Step 4:
We will try the fourth option
![\begin{gathered} y=2x+1 \\ y=2(1)+1 \\ y=2+1 \\ y=3 \\ (1,3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o4d5f1coid10r9r1akzya4wygd3jok7fpb.png)
Hence,
The final answer is
![\Rightarrow y=x-2](https://img.qammunity.org/2023/formulas/mathematics/college/hcmkgqy2ktdyg3d62t5qsy1ojp59vuj5ex.png)